Variable clinical presentation of split hand/foot malformation syndrome in a family with microduplication of 10q24.32: a case report - Akimova, Daria; Markova, Tatiana; Ampleeva, Maria; Skoblov, Mikhail (Frontiers in Genetics, 2024)
SHFM (Split Hand/Foot Malformation) is a heterogeneous group of disorders characterized by the presence of clefts in the hands and feet, along with syndactyly of the digits. In this article, we describe a family in which two members exhibit characteristic developmental abnormalities associated with SHFM, presenting with variable clinical features. Using whole-genome sequencing, we identified a microduplication of a chromosomal segment on locus 10q24.32, specifically spanning positions 102934495 to 103496555, encompassing genes BTRC, POLL, FBXW4 and LBX1 in the proband. Genomic duplications, including these genes, were previously described in patients diagnosed with the third type of SHFM. We validated the presence of this structural rearrangement in 7 family members, including the proband and the proband's father. Remarkably, further investigation demonstrated that the detected duplication exhibits a mosaic state in the phenotypically normal paternal grandmother of the proband, thereby providing a plausible explanation for the absence of a pathological phenotype in her.